Dinamika Kelompok Tani Wana Agung Sejahtera di Desa Rejoagung, Kecamatan Sumberwringin, Kabupaten Bondowoso - Rokhani Rokhani; Angger Dwi Pangestu; Sudarko Sudarko; Lenny Luthfiyah (Universitas Sebelas Maret, 2025)
Dynamics of the Wana Agung Sejahtera Farmer Group in Rejoagung Village, Sumberwringin Sub-District, Bondowoso Regency. This research aims to analyze the dynamics of the Wana Agung Sejahtera Farmer Group in Rejoagung Village, Sumberwringin Sub-district, Bondowoso Regency. This research employs a qualitative descriptive approach, grounded in the theory of Johnson and Johnson. Informants were selected purposively, and data were obtained through in-depth interviews and documentation. Data were analyzed using the method by Miles, Huberman, and Saldana. The results describe the dynamics of the Wana Agung Sejahtera Farmers Group in terms of 7 key elements: group goals, group communication, leadership, decision-making, power utilization, creativity, and conflict management. Two elements show dynamics, namely creativity and power utilization. The element of power utilization in the aspect of group norms includes an unwritten rule regarding member attendance in group activities. The consequence is that members are reprimanded by other members and may receive punishment in the form of social sanctions, such as being ignored or subtly criticized during activities. The creativity element in the aspect of developing creativity demonstrates that the Wana Agung Sejahtera Farmers Group, which initially had limited knowledge about proper coffee cultivation and market access, has now acquired the necessary knowledge and is able to develop creativity in terms of proper coffee cultivation and market access.